A Historical Analysis of the Nexus between Water Supply and Disease Control in Western Nigeria, 1900-1945 - Onobhayedo, Albert O. (NIU Journal of Social Sciences, 2022)
This study examines the correlation between the supply of hygienic water and disease control in Western Nigeria. Focusing on the early years of colonial rule, 1900 to 1945, it interrogates the intersection between the indigenous and colonial modes of water supply and, therefore, illuminates the peculiarities and preferences of both dispensations. Beyond the realm of urbanisation, the study situates the supply of water in Western Nigeria within the context of medical history. Accordingly, it discusses the impact of unhygienic water on the prevalence of diseases such as diarrhoea, dysentery, guinea worm and typhoid fever in the area. The study shows the efforts made by the colonial authorities to introduce scientific parameters into the sourcing of water for domestic use, the challenges that beset the process, their lopsided focus on the larger towns where colonial administrators, missionaries and merchants mostly resided and the relative neglect of the rural areas. The study relies mainly on primary sources, especially data obtained from the National archives, Ibadan, which were subjected to historical analysis. This focus on the impact of water supply on the outbreak of diseases and the earliest search for hygienic water in Western Nigeria, provides a research base for subsequent studies in related themes in Nigerian medical history. Keywords : Western Nigeria, Colonial, Water supply, Diseases, Healthcare.